2014
DOI: 10.14207/ejsd.2014.v3n2p33
|View full text |Cite
|
Sign up to set email alerts
|

Oil Price and Stock Market: Empirical Evidence from Nigeria

Abstract: This paper examined the relationship between changes in oil prices and stock market growth over the period 1981-2011 using vector error correction modeling approach. The results suggest a long run relationship between oil price, exchange rate and stock market growth. A unidirectional causality runs from oil price change to stock market development. The impulse response function shows that oil price has a temporary positive impact on stock market. The VDC shows that stock market development to be very much depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 20 publications
1
12
1
Order By: Relevance
“…Various studies on the effect of crude oil price fluctuation on the stock market in Nigeria show mixed results. For instance, Omisakin et al (2009), Mordi et al (2010), Abbas and Terfa (2010), Adebiyi et al This Journal is licensed under a Creative Commons Attribution 4.0 International License (2010), Akomolafe and Danladi (2014), Akinlo (2014), Iheanacho (2016), Lawal et al (2018), Soyemi et al (2017), Ojikutu et al (2017), Obi et al (2018) observe a positive effect of oil price shock on the stock price. On the contrary, studies like Adaramola (2012) and Effiong (2014) reported an inverse correlation between the price of oil movements and returns from stocks.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies on the effect of crude oil price fluctuation on the stock market in Nigeria show mixed results. For instance, Omisakin et al (2009), Mordi et al (2010), Abbas and Terfa (2010), Adebiyi et al This Journal is licensed under a Creative Commons Attribution 4.0 International License (2010), Akomolafe and Danladi (2014), Akinlo (2014), Iheanacho (2016), Lawal et al (2018), Soyemi et al (2017), Ojikutu et al (2017), Obi et al (2018) observe a positive effect of oil price shock on the stock price. On the contrary, studies like Adaramola (2012) and Effiong (2014) reported an inverse correlation between the price of oil movements and returns from stocks.…”
Section: Introductionmentioning
confidence: 99%
“…However, it contradicts with the findings of Dawson (2007); Oberndorfer (2009); Basher et al (2012); Movahedizadeh et al (2014); Degiannakis et al (2017); Akinlo (2014); Gupta (2016); Putra and Robiyanto (2019) and Antono et al (2019) which demonstrates that there is a significant influence of world oil and gas prices on stock return in short and long-term. Then Boyer and Filion (2004) argued that oil prices impact stock markets in the mining sector.…”
Section: Oil Price Has a Significant Effect On The Stock Return Of Mining Sectormentioning
confidence: 70%
“…Itotenaan et al (2013) investigated the relationship between oil prices and stock market performance in Nigeria using different empirical methods which include the Vector error correction model (VECM) and the Vector auto regression (VAR) model. Akinlo (2014) examined the relationship between changes in oil prices and stock market growth over the period 1981-2011 using the vector error correction modeling approach which suggested a long run relationship between oil price, exchange rate and stock market growth. The study seeks to examine the impact of oil prices on stock market development in selected Sub-Sahara African (SSA) oil producing countries from 1989 to 2015.…”
Section: Literature Reviewmentioning
confidence: 99%